Infectious Risk in the Sterilization Process for Reusable Medical Devices: Preliminary Risk Analysis (Asian Journal of Pharmaceutics (AJP), 2023)
Background: Patient safety is an area of health care that has emerged with the increasing complexity of health-caresystems. Indeed, there are several arguments for a comprehensive and coordinated approach to risk management.This study determines all probable hazards, which may generate an infectious risk during the different steps of thesterilization process. Materials and Methods: The study was conducted from November to December 2019 inthe central sterilization department of the IBN Sina Hospital in Rabat. The method adopted was the preliminaryrisk analysis (PRA) applied to reusable medical devices (DM) circuits. Results: A total of 38 dangerous situationsgenerating an infectious accident were revealed, which will make 38 scenarios. The mapping of hazardoussituations relating to the different phases of the sterilization process showed 5 types of generic hazards. Amongthese 38 scenarios, 9 are in criticality class 3, 21 situations are in criticality class 2, and 8 scenarios are in criticalityclass 1. After the implementation of risk reduction actions, 31 scenarios remain in criticality 1, 7 in criticality 2,and no scenario in criticality 3. Conclusion: The PRA method has enabled all phases of the sterilization processto be analyzed and all the probable hazards that could lead to an infectious accident to be identified. The proposedrisk reduction measures are organizational and educational. After the implementation of these measures, all themaximum risks are reduced to a tolerable zone under control, and the average risks are reduced.